Application of TCM for Partial-Response Channel In HDTV - 仇佩亮; 汪晓阳 (Tongxin xuebao)
This paper describes rejection of the co-channel interference due to the PAL-D picture carrier,colour sub-carrier and sound carrier and compares the symbol-by-symbol detection method with MLD method in a system G（D）=1+D￣k with an m-level input.Referencing to the Grand Alliance schem of U.S.A and combining with the practical situation of our country.this paper addresses the application of TCM for partial-response channel to the terrestrial broadcast transmission of digital HDTV signal.